Cultural Variations in the Relationship Between Anger Coping Styles, Depression, and Life Satisfaction. (April 2016) - Smith, Peter B.; Easterbrook, Matthew J.; Celikkol, Göksu Cagil; Chen, Sylvia Xiaohua; Ping, Hu; Rizwan, Muhammad
Hypotheses are tested that ways of handling anger and their consequences will differ in student samples drawn from dignity cultures (United Kingdom and Finland), honor cultures (Turkey and Pakistan), and face cultures (Hong Kong and China). In line with our hypotheses, holding anger in and controlling anger correlate positively in face cultures but not in other samples, whereas holding anger in and letting anger out correlate positively in honor cultures but not in other samples. Furthermore, holding anger in and letting anger out are more strongly predictive of high depression and low life satisfaction in honor cultures than in other samples. The results provide support for the cross-cultural validity of Spielberger's Anger Expression Inventory and for the proposition that differences in ways of handling anger can be understood in terms of contrasting cultural contexts.